2013
DOI: 10.1167/iovs.13-11765
|View full text |Cite
|
Sign up to set email alerts
|

Development of Refractive Error in Individual Children With Regressed Retinopathy of Prematurity

Abstract: The severe ROP group progressed rapidly toward myopia, particularly during the first 1.3 years; anisometropia and astigmatism also increased with age. The mild/no ROP group showed little change in refraction. Infants treated with laser photocoagulation for severe ROP should be monitored with periodic cycloplegic refractions and provided with early optical correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 43 publications
7
45
0
Order By: Relevance
“…Anisometropia and strabismus are the predominant risk factors for the development of amblyopia in children following laser ablation for severe ROP (28)(29)(30) . The present study demonstrated significantly higher rates of refractive anisometropia and strabismus following laser treatment compared to IVB monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Anisometropia and strabismus are the predominant risk factors for the development of amblyopia in children following laser ablation for severe ROP (28)(29)(30) . The present study demonstrated significantly higher rates of refractive anisometropia and strabismus following laser treatment compared to IVB monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Children with laser-treated severe ROP exhibited the highest prevalence of myopia. Wang et al [23] conducted a similar longitudinal prospective study and found that the prevalence, magnitude, and rate of myopic progression were significantly higher in the severe ROP group treated by laser than in the moderate/no ROP group. Eyes in the severe ROP group progressed rapidly toward myopia, particularly during the first 1.3 years [23].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [23] conducted a similar longitudinal prospective study and found that the prevalence, magnitude, and rate of myopic progression were significantly higher in the severe ROP group treated by laser than in the moderate/no ROP group. Eyes in the severe ROP group progressed rapidly toward myopia, particularly during the first 1.3 years [23]. In the present study, it was also found that severe ROP eyes which received treatment developed myopia more frequently than eyes without ROP or with spontaneously regressed ROP at the age of 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies in the literature have reported the prevalence of refractive errors and strabismus in preterm infants at different stages of growth 10,11. In particular, several authors described the impact of myopia and its association with prematurity 12,13.…”
Section: Introductionmentioning
confidence: 99%